2012
DOI: 10.4172/2161-1009.1000113
|View full text |Cite
|
Sign up to set email alerts
|

Using of Coffee and Cardamom Mixture to Ameliorate Oxidative Stress Induced in γ-irradiated Rats

Abstract: Human exposure to ionizing radiation induced overproduction of free radicals leading to oxidative stress. This study aims to evaluate the possibility of using of coffee and cardamom mixture, as natural antioxidant compounds, to ameliorate the damage effect of oxidative stress. Phenolic contents in coffee and essential oils in cardamom were identified by using HPLC chromatography and GC/MS analysis. Four groups of adult male rats were used; the control group (A), the second group (B) received orally mixture ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 55 publications
0
19
0
1
Order By: Relevance
“…Similarly, another study documented that 1,8-cineole (10.7%), a-terpinyl acetate (44.3%), a-terpineol (9.8%), linalool (8.6%) were the major compounds of essential oil (Singh et al 2008). Hamzaa and Osman (2012) characterized the green cardamom essential oil using GC-MS and found a-terpenyl acetate (60.65%), 1,8-cineol (13.63%), and limonene (7.12%) as major components. Recently, hydro-distilled cardamom essential oil obtained through Clevenger-type apparatus was analyzed by GC-MS and the results are in line with the current study as they reported the principle components were a-terpinyl acetate (40.7%), 1,8-cineole (25.6%), and linalool (6.3%) (Savan and Kucukbay 2013).…”
Section: Characterization and Quantification Of Essential Oil Constitmentioning
confidence: 88%
“…Similarly, another study documented that 1,8-cineole (10.7%), a-terpinyl acetate (44.3%), a-terpineol (9.8%), linalool (8.6%) were the major compounds of essential oil (Singh et al 2008). Hamzaa and Osman (2012) characterized the green cardamom essential oil using GC-MS and found a-terpenyl acetate (60.65%), 1,8-cineol (13.63%), and limonene (7.12%) as major components. Recently, hydro-distilled cardamom essential oil obtained through Clevenger-type apparatus was analyzed by GC-MS and the results are in line with the current study as they reported the principle components were a-terpinyl acetate (40.7%), 1,8-cineole (25.6%), and linalool (6.3%) (Savan and Kucukbay 2013).…”
Section: Characterization and Quantification Of Essential Oil Constitmentioning
confidence: 88%
“…The explained mechanisms in the improvement of the liver enzymes and the degree of fatty liver by cardamom include decrease of lipid peroxidation, increase of antioxidant capacity, cardamom active contents including phenols, polyphenols, minerals (Cu, Mn) [ 59 , 60 , 67 , 68 , 89 – 91 ], 1,8-cineol [ 92 ], and flavonoids [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…These berries are not only used as fruits, but also have been used effectively as natural medicines to cure sore throat, fever, hypertension and anemia [16,17]. Moreover, white mulberry fruits widely distributed in Egyptian agriculture are used to protect from liver and kidney damage, strengthen the joints, improve eyesight, and have anti-aging and radio protective effects [15,18,19]. In addition, recent studies have reported that 1-deoxynojirimycin in white mulberry has anti-diabetic effects and it reduces postprandial blood glucose levels through inhibition of α-glucosidase and decrease of serum triglyceride levels [20,21].…”
Section: Introductionmentioning
confidence: 99%